Shared Diminished Reality: A New VR Framework for the Study of Embodied Intersubjectivity - Vuarnesson, Loup; Zamplaras, Dionysios; Laroche, Julien; Dumit, Joseph; Lutes, Clint; Bachrach, Asaf; Garnier, Francois (Frontiers in Virtual Reality, 2021)
Shaping both the environment and the embodiment of the users in that virtual world, VR offers designers and cognitive scientists the unprecedented potential to virtually explore a vast set of interactions between persons, and persons and their environment. By design, VR tools offer a formidable opportunity to revisit the links between body movement and lived experiences, and to experiment with them in a controlled, yet engaging and ecologically valid manner. In our multidisciplinary research-creation project we ask, how can we design (virtual) environments that specifically encourage interactions between multiple persons and that allow designers, scientists and participants (users or ‘immersants’) to explore the very process of interaction itself? Building on our combined experience with dance improvisation research and interactive virtual spatial design, we document a multi-user VR experience design approach we name Shared Diminished Reality (SDR), where immersants are co-present and able to move together while their bodies and the environment are represented in a minimalist way. Our working hypothesis is that non-anthropomorphic embodiment of oneself and one’s partner(s), combined with open-ended exploration, focus the user’s attention on the quality of the interaction and encourages playfulness and creativity. We present the Articulations VR platform and its design history, as well as design evaluations of SDR in a laboratory setting and through a mixed reality performance, interrogating the impact of our minimalist approach on user experience and on the quality of the interaction. Our results suggest that minimizing (self and other) representation in Shared Diminished Reality positively impacts relational dynamics, induces playful creativity and fosters the will to move and improvise together.